The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1055/s-2006-924711
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation after Coronary Artery Bypass Grafting in Elderly Patients: Incidence and Risk Factor Analysis

Abstract: This study of elderly patients reveals some novel predictors of post-CABG AF, most notably preoperative renal insufficiency and EuroSCORE. It is important to identify risk factors for post-CABG AF in all patient groups as this knowledge might lead to better prevention of this problem and its potential consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 14 publications
(23 reference statements)
4
41
0
2
Order By: Relevance
“…It takes into account general patient information, preoperative general and cardiac risk factors, and operative information. 12) Analysis of the data revealed that AF Group had a signifi cantly higher mean additive EuroSCORE score than Non-AF Group. Applying this risk-scoring model might make it possible to administer appropriate pharmacologic and non-pharmacologic prophylaxis before or after CABG, and thus reduce postoperative AF and its consequences.…”
Section: Discussionmentioning
confidence: 96%
“…It takes into account general patient information, preoperative general and cardiac risk factors, and operative information. 12) Analysis of the data revealed that AF Group had a signifi cantly higher mean additive EuroSCORE score than Non-AF Group. Applying this risk-scoring model might make it possible to administer appropriate pharmacologic and non-pharmacologic prophylaxis before or after CABG, and thus reduce postoperative AF and its consequences.…”
Section: Discussionmentioning
confidence: 96%
“…Advanced age was detected as an independent predictor of the development of AF in our study. Age-related changes, including atrial fi brosis and accumulation of amyloid, can cause intraatrial reentry, which leads to the development of AF (15). Age has been repeatedly shown to be the major risk factor for AF after cardiac surgery (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative renal insufficiency was defined as a serum creatinine level ≥1.5 mg/dL prior to coronary artery bypass surgery. 7) Patients are generally considered as having PAH when their mean PAP exceeds 25 mmHg at rest, and 30 mmHg during exercise. 8) Transthoracic echocardiographies were performed by the Cardiology Department of the Medical Faculty on the left lateral decubitus, the parasternal long axis, the parasternal short axis and the apical four chamber of the patients.…”
Section: Data Collection and Definitionsmentioning
confidence: 99%